2021
DOI: 10.1021/acs.jpclett.1c01798
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrational and Thermodynamic Properties of CsPbI3 Polymorphs: An Improved Description Based on the SCAN meta-GGA Functional

Abstract: We report the vibrational and thermodynamic properties of four known CsPbI 3 polymorphs in the framework of the density functional theory. We compare the recently introduced strongly constrained and appropriately normed (SCAN) meta-generalized gradient approximation (meta-GGA) with the local density approximation (LDA). We found that the SCAN, compared to the LDA, could explain discrepancies between theoretical and experimental results. Evaluating the Helmholtz free energy as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…Previously, Marronnier et al used the local density approximation (LDA) functional to obtain a double-well potential with an energy barrier of 7.3 meV for the cubic α-phase of CsPbI 3 from density functional perturbation theory calculations for the soft optical mode at Γ . Using the LDA, a recent study reported a double-well instability with a 5.1 meV barrier height in the α-CsPbI 3 , while the strongly constrained and appropriately normed (SCAN) meta-GGA functional did not show any anharmonicity at Γ but produced an accurate lattice constant . While the SCAN meta-GGA is known to yield accurate structural properties of MHPs, the absence of the double-well potential suggests that it cannot fully capture the octahedral tilting and the iodine displacement in MHPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Marronnier et al used the local density approximation (LDA) functional to obtain a double-well potential with an energy barrier of 7.3 meV for the cubic α-phase of CsPbI 3 from density functional perturbation theory calculations for the soft optical mode at Γ . Using the LDA, a recent study reported a double-well instability with a 5.1 meV barrier height in the α-CsPbI 3 , while the strongly constrained and appropriately normed (SCAN) meta-GGA functional did not show any anharmonicity at Γ but produced an accurate lattice constant . While the SCAN meta-GGA is known to yield accurate structural properties of MHPs, the absence of the double-well potential suggests that it cannot fully capture the octahedral tilting and the iodine displacement in MHPs.…”
mentioning
confidence: 99%
“…29 Using the LDA, a recent study reported a double-well instability with a 5.1 meV barrier height in the α-CsPbI 3 , while the strongly constrained and appropriately normed (SCAN) meta-GGA functional did not show any anharmonicity at Γ but produced an accurate lattice constant. 58 While the SCAN meta-GGA is known to yield accurate structural properties of MHPs, 35 the absence of the double-well potential suggests that it cannot fully capture the octahedral tilting and the iodine displacement in MHPs. Previous studies did analyze further the octahedral tilting by the LDA and GGA functionals with different flavors of dispersion correction schemes, 59 but without quantifying the anharmonicity.…”
mentioning
confidence: 99%
“…34 Comparing the complexities of the metastable polymorphs with the complexity of δ -CsPbI 3 ( I G,conf ( δ , Pnma ) = 3.240 bit pos −1 arity −1 ), it can be concluded that the thermodynamic stability of the δ -phase originates from enthalpic interactions which agrees with results from DFT calculations. 53 Nonetheless, it has recently been noted that CsPbI 3 shows a rather complicated temperature-dependent crystal chemistry and a more thorough analysis involves the treatment of partially occupied sites as it has been previously demonstrated. 32 For other examples of how complexities evolve along a polymorphic series, we would like to refer to some previous complexity studies on CaCO 3 's polymorphs 28 and the displacive phase transitions of [(MoO) 2 P 4 O 13 ].…”
Section: Resultsmentioning
confidence: 96%
“…Subsequently, single point energy and property evaluation are done using a more recently (2015) introduced meta-GGA functional, namely the Strongly Constrained and Appropriately Normed (SCAN) functional of Sun et al 38 The latter functional is particularly useful for thermodynamic calculations since it was recently demonstrated that this functional is better than GGA or local density approximation (LDA) functionals at predicting the lattice parameters and formation enthalpies of CsPbI 3 phases; it also did not show ferroelectric instability in the phonon spectra, unlike LDA which erroneously reported the material as ferroelectric. 39 SCAN has also been shown to yield reliable results for semiconductor bandgaps comparable to the widely used HSE hybrid functional 40 but at reduced computational cost. [41][42][43][44] By analyzing the formation energies of the various electron donating and accepting defects as a function of the Fermi energy, we found antisite defects, which are not previously studied, are in fact thermodynamically quite significant.…”
Section: Introductionmentioning
confidence: 99%